Socio-Cultural Problems of Working Women in the Media Industry of Hyderabad, Pakistan - Saeedah Shah; Aijaz Ali Wassan; Nagina Parveen (Progressive Research Journal of Arts & Humanities (PRJAH), 2022)
Pakistan is the country where women workers face socio-cultural problems in the every field. But media field is a level head that brings more problems and challenges for them. The several research papers conclude with findings that Pakistan is not a suitable country for media working women. The numerous working women in the media sector of Hyderabad were unattended. Sadly to write that there was no thorough research ever conducted on their sociocultural problems. Hence, the qualitative research, with a purposive sampling method was conducted on socio-cultural problems of working women. Initially, 40 participants’ list was prepared from both print and electronic media, but later 20 participants were purposively short-listed for in-depth interviews. Moreover, the interviews were recorded in local languages: Sindhi and Urdu. The research revealed that they were pressurized, hindered, and misbehaved when they came into the field of media. The study exhibited that family members’ prejudice and pressure, society’s bad comments and wrong perceptions, males’ stereotype thinking, and overload of work were the topmost socio-cultural problems that women face in their entire media career. Moreover, they are considered an immoral, and receive the fewer marriage proposals. Mostly media women face problems from their families. So, such the families should support and encourage them. Though laws are present, yet unimplemented. Law enforcement agencies should strictly implement the available laws that protect women inside and outside the working environment.